Malnutrition and Associated Factors with Nutritional Status among Orphan Children: An Evidence-Based Study from Nepal - Acharya, Shiva Raj; Adhikari, Shiksha; Pahari, Sandip; Shin, Yong Chul; Moon, Deog Hwan (International Journal of Child Health and Nutrition, 2020)
Background: Malnutrition is a common public health problem among children in low and middle-income developing countries. Orphan's children are vulnerable and neglected groups in society and are more prone to malnutrition. The study aims to identify the prevalence of underweight, stunting, thinness, and factors associated with nutritional status among orphan children. Methods: Quantitative method & analytical cross-sectional research design were used to assess the nutritional status and its associated factors among orphan children in Pokhara Valley, Nepal. The sample size of 160 children was obtained by a simple random technique. The semi-structured questionnaire, digital bathroom scale, stadiometer was used as the data collection technique. Data management and analysis were done from Epi-info, SPSS 25 version, and WHO Anthro plus. Findings: The majority of children were malnourished (80.6%) with the prevalence of stunting (55.1%), thinness (13.8%), and overweight (6.9%). Prevalence of underweight, stunting, and thinness was high among the boys (85.5%, 26.3%, and 15.8%), but overweight was more prevalent among the girls (7.1%). Ethnicity, sex, age, stay duration in an orphanage, and education of caregivers was associated with the nutritional status of orphan children (p <0.05). Non-privileged children and children below 11 years were more prone to malnutrition. Conclusion: Malnutrition is highly prevalent in orphan children and needs to be addressed. There is still limited study available on the nutritional status of orphan children in Nepal. Nutritional status should be monitored regularly for early identification and timely intervention of malnutrition to promote the nutrition health status of orphan children